Macrofloristic assemblage of the Paraná Formation (Middle-Upper Miocene) in Entre Ríos (Argentina) - Anzótegui, Luisa Matilde (2008)
The Paraná Formation represents the marine ingression of Middle-Upper Miocene that invaded the Pampean plain and parts of Argentinean Mesopotamia. In its outcroppings, an abundant fossil fauna and flora (palynomorphs, logs, foliar impressions and phytoliths) have been recognized. In Villa Urquiza locality (Entre Ríos Province, Argentina), the outcropping strata are constituted by white sands intermingled with pure clays, gray to grayish-green, with abundant diagonal and flat structures including paleochannels filled with clays. In this study, foliar impressions such as Myrciophyllum paranaesianum sp. nov.; Laurophyllum sp. (Lauraceae), and Schinus aff. terebinthifolia (Anacardaicaeae) are described. The assignment of Laurophyllum and Myrciophyllum and the existence of xerophytic forests are discussed. Taking into account both the habit and habitat of recent plant species related to the fossil material, it is concluded that forests with Podocarpaceae and Araucariaceae existed in higher altitude zones, represented by fossils in the marine environment of the Paraná Formation. It is considered that these species were part of a heterogeneous environment with highlands and flooded lowlands, as part of the Seasonally Dry Neotropical Forest. The climate would have been warm and humid and among the environmental units; there were hydrophylous and mesophylous forests, marshy environments, lentic and lotic aquatic communities. Considering plant leaf impressions and the communities they may represent, vegetation of the Paraná Formation is interpreted to be consistent with the Neotropical Paleophytogeographic Province.